Mangrove Propagule Dispersal And Early Growth Studies Of Avicennia Marina And Rhizophora Apiculata - Wong , Yun Yun (2012)

(untitled)
A study was conducted to investigate the propagule dispersal and early growth of two common species in Malaysia, Avicennia marina and Rhizophora apiculata. Field studies were carried out at Kuala Pulau Betong, a coastal mangrove area in the west coast of Penang Island. Movements of the mangrove propagules were monitored by the release and recapture method while their early growth were examined at the site by tethering system. Another “enforced dispersal” experiment was conducted under laboratory condition.